Analysis of the impact of soil excavation stages on slope stability case study of road and bridge construction projects in bts. Singaraja-Mengwitani at point 7E, Bali - Yudha, Guilden Laelatu; Soemitro, Ria Asih Aryani; Satrya, Trihanyndio Rendy; Fachrie, Noor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Singaraja - Pengayaman BTS Road Section is a national road located in the central corridor of Bali Island and includes several critical locations in terms of road geometry. Geometric adjustments are being addressed through the BTS Singaraja - Mengwitani Road and Bridge Construction Project Section 7E, involving excavation work up to 64 meters high at STA. 0+119.87. This study aims to analyze slope stability based on existing conditions, evaluate the impact of excavation method variations on slope stability, and determine effective excavation methods both with and without the influence of water on slope stability using Plaxis 2D program. The research results indicate that the safety factor (SF) value of the existing slope prior to excavation was 1.337, whereas it decreased to 1.034 after the final excavation stage. According to the SNI 8460:2017 standard (SF < 1.5), the slope condition in the final excavation stage is deemed unsafe. Excavations with depth variations of 1 meter, 2 meters, and 3 meters, as well as at slope angles of 45˚, 55˚, and 65˚, showed similar impacts on slope stability. A significant decrease in the safety factor occurred from the 7th excavation bench downward, where the safety factor fell below 1.3. At the end of the excavation process, the deepest sliding surface reached a depth of 20.11 meters. At an elevation of +36.5 meters, where the groundwater level reaches 56.40% of the total slope height, which marks the boundary between soil and rock layers, the safety factor drops to 1.040. Further increases in groundwater levels above +36.5 meters could render the slope unstable and potentially lead to collapse.